Bombay Islam : the religious economy of the West Indian Ocean, 18 40-1915 - Green, Nile. (Cambridge, UK ; New York : Cambridge University Press, 2011)
"As a thriving port city, nineteenth-century Bombay attracted migran ts from across India and beyond. Nile Green's Bombay Islam traces the t ies between industrialization, imperialism, and the production of relig ion to show how Muslim migration from the oceanic and continental hinte rlands of Bombay in this period fueled demand for a wide range of relig ious suppliers, as Christian missionaries competed with Muslim religiou s entrepreneurs for a stake in the new market. Enabled by a colonial po licy of non-intervention in religious affairs, and powered by steam tra vel and vernacular printing, Bombay's Islamic productions were exported as far as South Africa and Iran. Connecting histories of religion, lab our, and globalization, the book examines the role of ordinary people m ill hands and merchants in shaping the demand that drove the market. By drawing on hagiographies, travelogues, doctrinal works, and poems in P ersian, Urdu, and Arabic, Bombay Islam unravels a vernacular modernity that saw people from across the Indian Ocean drawn into Bombay's indust rial economy of enchantment"--
Includes bibliographical references (p. 287-316) and index.
Keywords: Internal migrants -- India -- Bombay -- History; Muslims -- India -- Bombay -- History; Iranians -- India -- Bombay -- History; Bombay (India) -- Commerce -- History